2005
DOI: 10.1016/j.cell.2005.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Microscopy Reveals Plasma Membrane Microdomains Created by Protein-Protein Networks that Exclude or Trap Signaling Molecules in T Cells

Abstract: Membrane subdomains have been implicated in T cell signaling, although their properties and mechanisms of formation remain controversial. Here, we have used single-molecule and scanning confocal imaging to characterize the behavior of GFP-tagged signaling proteins in Jurkat T cells. We show that the coreceptor CD2, the adaptor protein LAT, and tyrosine kinase Lck cocluster in discrete microdomains in the plasma membrane of signaling T cells. These microdomains require protein-protein interactions mediated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
670
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 713 publications
(723 citation statements)
references
References 68 publications
38
670
1
5
Order By: Relevance
“…The conclusion of Larson et al 41 is that a protein-interaction domain, provided by the activated kinase domain of Lyn, is required for stable association with the crosslinked-IgE receptor. A similar conclusion is equally plausible in the case of interactions between activated LCK with the TCR-signalling domain 31 . Analysis of the microlocalization of the minimal anchors of Lyn and LCK and the cognate full-length proteins has largely relied on detergent insolubility with all its inherent problems (BOX 2), except for a FRET study that showed cholesterol-dependent clustering of the minimal Lyn anchor 29 .…”
Section: Determinants Of Raft Stabilitymentioning
confidence: 52%
See 3 more Smart Citations
“…The conclusion of Larson et al 41 is that a protein-interaction domain, provided by the activated kinase domain of Lyn, is required for stable association with the crosslinked-IgE receptor. A similar conclusion is equally plausible in the case of interactions between activated LCK with the TCR-signalling domain 31 . Analysis of the microlocalization of the minimal anchors of Lyn and LCK and the cognate full-length proteins has largely relied on detergent insolubility with all its inherent problems (BOX 2), except for a FRET study that showed cholesterol-dependent clustering of the minimal Lyn anchor 29 .…”
Section: Determinants Of Raft Stabilitymentioning
confidence: 52%
“…Analysis of the microlocalization of the minimal anchors of Lyn and LCK and the cognate full-length proteins has largely relied on detergent insolubility with all its inherent problems (BOX 2), except for a FRET study that showed cholesterol-dependent clustering of the minimal Lyn anchor 29 . The new studies 31,41 show that the surface distribution of the minimal anchor and the full-length proteins are different, and therefore illustrate the importance of protein-protein as well as anchor-lipid-bilayer interactions in controlling the stable association of proteins with L o domains.…”
Section: Determinants Of Raft Stabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Protein diffusion during T-cell signaling, another example of a signaling event thought to involve lipid rafts, has also been investigated using single molecule techniques. This approach revealed an unexpected role of protein-protein networks in regulating the enrichment or exclusion of proteins from sites of T-cell signaling (Douglass and Vale 2005).…”
Section: Methods For Studying Lipid Rafts In Cells and Artificial Memmentioning
confidence: 99%